Psychological Support to the Community During the COVID-19 Pandemic: Field Experience in Reggio Emilia, Northern Italy - Ghiretti, Fiorello; Gildoni, Gabriela; Grassi, Gaddo Maria; Torricelli, Laura; Benassi, Elena; Bonaretti, Elisa; Bonazzi, Francesca; Borelli, Sara; Cagnolati, Francesca; Covati, Katia; Errera, Francesca; Finardi, Vanessa; et al. (Frontiers in Psychology, 2020)
We report the field experience of the psychological staff of Azienda USL-IRCCS di Reggio Emilia, a local health system conglomerate serving half a million inhabitants within a catchment area of the Emilia Romagna Region of Italy, during the coronavirus (COVID-19) pandemic. We provided free telephone-based psychological support for the community, with the specific aim of reducing stress caused by the COVID-19 pandemic and its consequences, such as quarantine and lock-down. We describe how the community used this opportunity of psychological support in terms of problems reported and interventions provided. Our field experience suggests that a service of phone psychological support is feasible and quickly implementable in the case of sudden emergencies that affect, to different extents, the whole community.